CuI‐Catalyzed Pentafluoroethylation of Aryl Iodides in the Presence of Tetrafluoroethylene and Cesium Fluoride: Determining the Route to the Key Pentafluoroethyl CuI Intermediate. Issue 39 (13th June 2018) - Ohashi, Masato; Ishida, Naoyoshi; Ando, Kota; Hashimoto, Yu; Shigaki, Anna; Kikushima, Kotaro; Ogoshi, Sensuke
Abstract: The Cu(I)‐catalyzed pentafluoroethylation of iodoarenes via the fluorocupration of tetrafluoroethylene (TFE) is disclosed. The active species, (phen)CuC2 F5, was isolated and its molecular structure confirmed by a single‐crystal X‐ray diffraction analysis. The key to the successful suppression of the competing oligomerization of TFE is to refrain from stirring the reaction mixture. A mechanistic study clearly discarded the possibility that the catalytic reaction proceeds via a radical pathway. Abstract : Don′t stir the pot : The Cu I ‐catalyzed pentafluoroethylation of iodoarenes via the fluorocupration of tetrafluoroethylene (TFE) is disclosed. The active species, (phen)CuC2 F5, was isolated and its molecular structure confirmed by a single‐crystal X‐ray diffraction analysis. The key to the successful suppression of the competing oligomerization of TFE is to refrain from stirring the reaction mixture. A mechanistic study clearly discarded the possibility that the catalytic reaction proceeds via a radical pathway.